2017
DOI: 10.1007/s12649-017-0166-9
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Scale Use of Compost Combined with Sorbents to Phytostabilize Ni-Contaminated Soil Using Lolium perenne L.

Abstract: Purpose An experiment was conducted to evaluate the potential use of a combination of food waste compost with sorbents as immobilizing agents to aid the phytostabilization of Ni-contaminated soil, using Lolium perenne L. (L. perenne). Methods The content of Ni in plants, i.e. total and extracted by 0.01 M CaCl 2 , was determined using the spectrophotometry method. Tests for the phytotoxicity of food waste compost were carried out using Phytotoxkit ™ tests. Results The compost phytotoxicity tests showed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 57 publications
0
6
0
1
Order By: Relevance
“…The germination index (IG) test is particularly popular, being used in studies concerning the assessment of compost maturity [16,17]. Justification for the application of this test was stressed by Bae et al [18] who reported that germination as the first stage of seed contact with the surrounding environment is a good indicator of their sensitivity to changing environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The germination index (IG) test is particularly popular, being used in studies concerning the assessment of compost maturity [16,17]. Justification for the application of this test was stressed by Bae et al [18] who reported that germination as the first stage of seed contact with the surrounding environment is a good indicator of their sensitivity to changing environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of metals in the presence of oxalic acid significantly increased the Pb and Zn content in leaf and the shoot of Sedum alfredii . Radziemska, Vaverkova, and Mazur (2019) studied the treatment of Ni contaminated soils using phytoremediation supplemented with compost. Lolium perenne L. ( L. perenne ) with compost (25%) enhanced root growth, while Ni accumulation occurred mainly in the roots.…”
Section: Biological Treatmentmentioning
confidence: 99%
“…Livestock and poultry (LP) manures and crop straws, as major AOWs [9], have been the focal points in recycling. Many scholars have explored the recycling methods [10,11] and utilization technologies [12][13][14] of these AOWs. Currently, AOWs are mostly recycled by composting [15,16] and biogas fermentation [17,18].…”
Section: Introductionmentioning
confidence: 99%